2015
DOI: 10.1016/j.conb.2014.12.012
|View full text |Cite
|
Sign up to set email alerts
|

Resolution revolution: epilepsy dynamics at the microscale

Abstract: Our understanding of the neuronal mechanisms behind epilepsy dynamics has recently advanced due to the application of novel technologies, monitoring hundreds of neurons with single cell resolution. These developments have provided new theories on the relationship between physiological and pathological states, as well as common motifs for the propagation of paroxysmal activity. While traditional electroencephalogram (EEG) recordings continue to describe normal network oscillations and abnormal epileptic events … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Identifying properties of seizure producing networks (“ictal networks”) may enable more efficient seizure control (Baraban and Loscher, 2014; Krook-Magnuson and Soltesz, 2015). Recent advances in mapping ictal network dynamics at the microscale have unveiled unexpected complexity (Bower et al, 2012; Cymerblit-Sabba and Schiller, 2012; Feldt Muldoon et al, 2013; Keller et al, 2010; Truccolo et al, 2014; Truccolo et al, 2011), challenging the classical view of epilepsy as a condition of stereotyped ictal events (Szabo et al, 2015). In fact, the monitoring of the recruitment of neural populations to successive seizures in humans using multi-electrode arrays has led to contrasting conclusions suggesting either strict reproducibility of neuronal spiking patterns (Truccolo et al, 2011), or lack of such reproducibility close to the epileptic focus (“ictal penumbra”, or “propagation area”) (Schevon et al, 2012) or completely non-repeated recruitment patterns (Bower et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Identifying properties of seizure producing networks (“ictal networks”) may enable more efficient seizure control (Baraban and Loscher, 2014; Krook-Magnuson and Soltesz, 2015). Recent advances in mapping ictal network dynamics at the microscale have unveiled unexpected complexity (Bower et al, 2012; Cymerblit-Sabba and Schiller, 2012; Feldt Muldoon et al, 2013; Keller et al, 2010; Truccolo et al, 2014; Truccolo et al, 2011), challenging the classical view of epilepsy as a condition of stereotyped ictal events (Szabo et al, 2015). In fact, the monitoring of the recruitment of neural populations to successive seizures in humans using multi-electrode arrays has led to contrasting conclusions suggesting either strict reproducibility of neuronal spiking patterns (Truccolo et al, 2011), or lack of such reproducibility close to the epileptic focus (“ictal penumbra”, or “propagation area”) (Schevon et al, 2012) or completely non-repeated recruitment patterns (Bower et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…An ongoing debate regards the dynamics of neuronal firing in the ictogenic network (Szabo et al, 2015 ). Decades of electrophysiological studies established the classical view of epileptic seizures as hypersynchronous and stereotyped events (McCormick and Contreras, 2001 ).…”
Section: Outlook: Open Questions To Design New Therapeutic Strategiesmentioning
confidence: 99%
“…For instance, high-resolution recordings at the meso-scale, which are currently highly tractable, offer the potential to infer neural population firing rates because it has been demonstrated that broadband local field potential power is proportional to local firing rates [33,34]. However, to validate methods that integrate between spatial scales, we need higher spatial resolution electrophysiological recordings [35,36]. Here, we briefly review the current state of the art in high-resolution electrode arrays and consider how high-resolution arrays can be useful for seizure prediction.…”
Section: High-spatial Resolution Measurementsmentioning
confidence: 99%